2007
DOI: 10.1007/s10643-007-0201-8
|View full text |Cite
|
Sign up to set email alerts
|

Starting School: Welcoming Young Children and Families into Early School Experiences

Abstract: Throughout the world, young children and their families anticipate the start of school with expectations and hopes, as well as concerns. Although the approaches and customs differ from one nation, region, or culture to another, one constant is the recognition that a collaborative effort is needed to welcome young children and their families into formal schooling experiences. The transition process should be proactive and responsive to the children's needs. This article addresses four key components of appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
1
6
0
1
Order By: Relevance
“…Dockett and Perry's (2004b) findings articulated discernible differences between the experiences and perspectives of children and parents, and highlighted the important implications of this when creating partnerships between schools and families. Similar findings emerged in a study by Laverick (2008), which emphasised the need to account for these differences within the transition process. Both in terms of policy and practice, the repositioning of the parents and families as active actors and agents during the transition process now sees family involvement increasingly recognised and called for in the development of transition programs (Bonhan-Baker & Little, 2004;Dockett, 2008;McInnes & Nichols, 2011).…”
Section: Conducting the Analysissupporting
confidence: 76%
“…Dockett and Perry's (2004b) findings articulated discernible differences between the experiences and perspectives of children and parents, and highlighted the important implications of this when creating partnerships between schools and families. Similar findings emerged in a study by Laverick (2008), which emphasised the need to account for these differences within the transition process. Both in terms of policy and practice, the repositioning of the parents and families as active actors and agents during the transition process now sees family involvement increasingly recognised and called for in the development of transition programs (Bonhan-Baker & Little, 2004;Dockett, 2008;McInnes & Nichols, 2011).…”
Section: Conducting the Analysissupporting
confidence: 76%
“…The earliest and most influential evidence that preschool matters comes from studies undertaken in the United States which reported positive outcomes for children attending the Perry Preschool programme, Head Start and the Bureau for the Education of the Handicapped, begun in 1965 (Schweinhart, Weikart andLarner 1986). International evidence for the effectiveness of preschool provision is supported by studies exploring school readiness in Australia (Dockett and Perry 2007a, 2007b, the USA (Laverick 2008), Iceland (Winter 2011) and Ireland (Kiernan et al 2008;O'Kane and Hayes 2006).…”
Section: School Readinessmentioning
confidence: 99%
“…When young children start school, it is important that the impressions they have of the school environment are positive. These impressions can last, and as such, can have an ongoing impact on how children perceive school (DEECD, 2009;Dockett & Perry, 2004;Laverick, 2007;Love, Logue, Trudeau & Thayer, 1992). This is particularly true of children who come from families with complex needs (Rosier & McDonald, 2011).…”
Section: Introductionmentioning
confidence: 99%